FUNCTIONAL NEUROLOGICAL SYMPTOM DISORDER (FNSD) ASSESSMENT AND TREATMENT: A CLINICAL CASE STUDY - Roohee, Amber (Journal of Arts & Social Sciences, 2024)
Abstract The patient was 30 years old, christian, married housewife with 4 kids, and educated up till 8th class. She visited to Psychiatry Department of Lahore General Hospital, Lahore with presenting complaints of headaches, dizziness, fits of unconsciousness, jerky movements during fits, muscular tension, low mood, anger, talk like a child, body aches and disturbed sleep. She was referred to the trainee clinical psychologist for psychological assessment and management of her symptoms. Informal assessment was done by using clinical interview, mental status examination and baseline charts of symptoms.Formal assessment was done by using Beck Depression Inventory (Beck,1961), DSM-5 TR symptom checklist of Functional Neurological Symptoms Disorder, Slossan Drawing Coordination Test (Slosson,1967) and Rotter Incomplete Sentence Blank (Rotter,1950). After careful formal and informal assessment the patient’s current diagnosis was (Functional Neurological Symptoms Disorder) Conversion Disorder (F44.7) mixed symptoms with stressors and in acute phase.Her case was conceptualized by Looper and Kermayer (2002) model.The CBT and psychodynamic techniques used to treat like psycho-education, fit record chart, deep breathing, progressive muscle relaxation, extinction, differential reinforcement,daily thought record, identifying cognitive errors, cost-benefit analysis, anger management, problem solving and free association. Post assessment analysis showed that the patient had shown 70% improvement in her symptoms after 12 psychotherapeutic sessions.